2015
DOI: 10.1111/nph.13273
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and mixing of old and new nonstructural carbon in two temperate trees

Abstract: We know surprisingly little about whole-tree nonstructural carbon (NSC; primarily sugars and starch) budgets. Even less well understood is the mixing between recent photosynthetic assimilates (new NSC) and previously stored reserves. And, NSC turnover times are poorly constrained. We characterized the distribution of NSC in the stemwood, branches, and roots of two temperate trees, and we used the continuous label offered by the radiocarbon (carbon-14, 14C) bomb spike to estimate the mean age of NSC in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 40 publications
6
102
1
Order By: Relevance
“…, Richardson et al. ), which agrees well with evidence that older NSC may be less available, or even unavailable, to trees compared to more recently fixed carbohydrates (Millard et al. , Sala et al.…”
Section: Discussionsupporting
confidence: 83%
“…, Richardson et al. ), which agrees well with evidence that older NSC may be less available, or even unavailable, to trees compared to more recently fixed carbohydrates (Millard et al. , Sala et al.…”
Section: Discussionsupporting
confidence: 83%
“…8). This view is supported by several studies showing that starch is more depleted than SS under lethal drought (Adams et al 2013, Mitchell et al 2013, Sevanto et al 2014, Dickman et al 2015, Garcia-Forner et al 2016, and by modeling and empirical results indicating that NSC has two distinct pools with different turnover times (Richardson et al 2013(Richardson et al , 2015. This view is supported by several studies showing that starch is more depleted than SS under lethal drought (Adams et al 2013, Mitchell et al 2013, Sevanto et al 2014, Dickman et al 2015, Garcia-Forner et al 2016, and by modeling and empirical results indicating that NSC has two distinct pools with different turnover times (Richardson et al 2013(Richardson et al , 2015.…”
Section: Hypothesis 4: Plants Rarely Deplete Their Nscmentioning
confidence: 73%
“…Wood, does not necessarily meet the well mixed assumption, so its particles may not have the same probability to leave the compartment at all times. Richardson et al (2015) 20 found a low concentration of old NSC in old rings of stemwood, and a high concentration of old NSC in coarse roots and fine roots of pine. Additionally, they found young and old C in roots.…”
mentioning
confidence: 99%
“…Additionally, they found young and old C in roots. These dynamics were interpreted as poor C mixing and reserves that turn over on different timescales (Richardson et al, 2015), but they may also obey to physiological constraints;…”
mentioning
confidence: 99%
See 1 more Smart Citation